Application of Pedrail Powered Support on Strata Control in Short-Wall Coal Mining. (31st March 2022) - Ma, Jingong; Ding, Yongcheng; Zhang, Hongwei
Abstract : In this study, the role of the pedrail powered (PP) support produced in China in the Wongawilli short-wall mining was explored, and the process from its import and introduction to its localization and use effect were detailed. The influences of the gob side and the solid-coal side on the pillar pressure were numerically simulated by exploring the working resistance of PP support at different locations and under different widths of pillar between mining caves (PMC) of the same branch lane during mining and investigating the pressure distribution and variations of each single pillar. The main influencing factors and their relationships with the working resistance were derived accordingly. Finally, key processing technologies to solve the problem of PP support crushing in the crushed zone were analyzed. The results suggest that the rated working resistance of PP support satisfies the requirement for use, and the roof of the branch lane behind the cutting roof line does not collapse, which ensures the safety of short-wall mining. The gob-side pressure is notably higher than the solid-coal-side pressure. When the PP support undergoes a support crushing accident, it can be pulled out by jointly adopting four key technologies, i.e., reinforced support to the roof, reinforcing rib support and ground bolt support for caving gangue piles, roof and loose body reinforcement by grouting, and traction by a prop-pulling winch.